Peer-to-Peer Solar and Social Rewards: Evidence from a Field Experiment - Stefano Carattini; Kenneth Gillingham; Xiangyu Meng; Erez Yoeli (Center for Economic Studies and ifo Institute (CESifo), 2022)
Observability has been demonstrated to influence the adoption of pro-social behavior in a variety of contexts. This study implements a field experiment to examine the influence of observability in the context of a novel pro-social behavior: peer-to-peer solar. Peer-to-peer solar offers an opportunity to households who cannot have solar on their homes to access solar energy from their neighbors. However, unlike solar installations, peer-to-peer solar is an invisible form of pro-environmental behavior. We implemented a set of randomized campaigns using Facebook ads in the Massachusetts cities of Cambridge and Somerville, in partnership with a peer-to-peer company. In the campaigns, treated customers were informed that they could share "green reports" online, providing information to others about their greenness. We find that interest in peer-to-peer solar increases by up to 30% when "green reports," which would make otherwise invisible behavior visible, are mentioned in the ads.
Keywords: C93; D91; Q20; 330; peer to peer solar; pro-environmental behavior; social rewards; visibility; Facebook